Implementasi Kepemimpinan Kepala Madrasah pada Masa Pandemi di Madrasah Aliyah Swasta Darul Ikhwan - Feby Hartika Putri (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2023)
This study aims to describe the implementation of school principal leadership during the Covid-19 pandemic at Madrasah Aliyah Swasta (MAS) Darul Ikhwan. This research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. Data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the school principal of MAS Darul Ikhwan carried out leadership functions through planning, implementation, supervision, and evaluation. The leadership style applied tended to be transformational, manifested in individualized consideration, inspirational motivation, intellectual stimulation, and idealized influence through discipline and role modeling. Furthermore, cultural, environmental, and regulatory factors influenced leadership effectiveness. The school’s religious culture, parental trust and support, as well as government and pesantren regulations shaped an adaptive and participatory leadership pattern. This study highlights that school leadership during the pandemic was not merely bureaucratic but also transformative. The implication suggests the need to strengthen principals’ capacities in crisis-based leadership, digital literacy, and change management to maintain educational quality in times of emergency.